Injection-seeded high-repetition-rate short-pulse micro-laser based on upconversion nanoparticles. Issue 2 (23rd December 2020) - Jiao, Jiannan; Zhou, Donglei; Li, Shufan; Low, Mun Ji; Gao, Yi; An, Jianing; Su, Pei-Chen; Kim, Seung-Woo; Kim, Seungchul; Kim, Kyujung; Suchand Sandeep, C. S.; Kim, Young-Jin
Abstract : We report a high-repetition-rate, short-pulse, upconversion micro-laser prepared by the fast thermal quenching of lanthanide-doped upconversion nanoparticles (UCNPs). Abstract : We demonstrate a high repetition-rate upconversion green pulsed micro-laser, which is prepared by the fast thermal quenching of lanthanide-doped upconversion nanoparticles (UCNPs) via femtosecond-laser direct writing. The outer rim of the prepared upconversion hemi-ellipsoidal microstructure works as a whispering-gallery-mode (WGM) optical resonator for the coherent photon build-up of third-harmonic ultra-short seed pulses. When near-infrared (NIR) femtosecond laser pulses of wavelength 1545 nm are focused onto the upconversion WGM resonator, the optical third-harmonic is generated at 515 nm together with the upconversion luminescence. The weak third-harmonic (TH) seed pulses are coherently amplified in the hemi-ellipsoidal upconversion resonator as a result of the resonant interaction between the incident femtosecond laser field, the TH, the upconversion luminescence and the WGM. This upconversion lasing preserves the original repetition rate of the NIR pump laser and the output polarization state is also coherently aligned to the pump laser polarization. Because of the isotropic nature of the upconversion micro-ellipsoids, the upconversion lasing shows maximum intensity with a linearly polarized pump beam and minimum intensity with a circularly polarized pump beam. Our scheme devised for realizing high-repetition-rate lasing at higher photon energies in a compact micro platform will open up new ways for on-chip optical information processing, high-throughput microfluidic sensing, and localized micro light sources for optical memories.